ORGANIZATION OF WEIGHT LIFTING CLUBS IN HIGHER EDUCATIONAL INSTITUTIONS AND MONITORING OF STUDENTS' PHYSICAL FITNESS - Nematov Soyib Teshayevich (International Journal of Literature and Language Studies, 2026)
This article examines the role and significance of kettlebell lifting sports clubs in improving the physical fitness level of student youth in higher education institutions. During the research, the dynamics of development of physical qualities, particularly strength and strength endurance of students involved in kettlebell lifting clubs, were analyzed based on pedagogical monitoring. The article develops organizational and methodical bases for organizing club activities, as well as criteria for monitoring and evaluating students' physical fitness. The results of long-term monitoring demonstrated the positive impact of kettlebell lifting exercises on the physical condition of students, on the basis of which practical recommendations were formulated.